Prognostic nutritional index as a predictor of in-hospital mortality in neonates and infants undergoing cardiac surgery - Gu, Xiaolin; Li, Jie; Huang, Xiaoqin; Bao, Rongxing; He, Hailin; Li, Liuyuan; Luo, Dandong; Zhang, Chongjian (Frontiers in Nutrition, 2025)
ObjectiveThe prognostic nutritional index (PNI), combining nutritional and systemic inflammation markers is suggested as a predictor of negative outcomes post-cardiac surgery. This study investigated the link between PNI and in-hospital mortality in neonates and infants undergoing cardiac surgery.MethodsThis retrospective cohort study included 3,082 neonates and infants (aged ≤ 365 days) who underwent primary cardiac surgery between January 2017 and October 2023. The PNI was utilized to evaluate nutritional status. Patients were stratified into two groups based on PNI values: low (PNI ≤ 51.65) and high (PNI > 51.65).The association between PNI and in-hospital mortality was assessed using multivariable logistic regression models, adjusted for demographic, preoperative, and surgical variables. Subgroup analyses were performed to assess potential effect modification. The potential linear relationship between PNI and mortality was examined using generalized additive models and smooth curve fitting.ResultsThe overall in-hospital mortality rate was 1.72% (53/3, 082). Patients with a PNI ≤ 51.65 exhibited a significantly higher mortality rate of 6.03% compared to 0.92% for those with a PNI > 51.65 (p < 0.001). Multivariable analysis identified PNI as an independent predictor of in-hospital mortality (adjusted odds ratio: 0.95; 95% CI: 0.91–0.98; p = 0.005). Subgroup analyses revealed significant effect modification by age, congenital heart disease (CHD) complexity, and cardiopulmonary bypass status (p for interaction < 0.05). The inverse relationship between PNI and mortality was stronger in neonates aged 30 days or younger, patients with non-complex CHD, and those undergoing off-pump surgery. Receiver operating characteristic analysis indicated that PNI effectively predicted in-hospital mortality, with an area under the curve of 0.745 (95% CI: 0.675–0.815; p < 0.001) and an optimal cutoff value of 51.65 determined by the Youden index.ConclusionsPNI independently predicts in-hospital mortality in neonates and infants undergoing cardiac surgery. The findings indicate that PNI could be an efficient tool for preoperative risk assessment in high-risk populations.